Práticas transdisciplinares na rede pública de ensino - Ramos, Steve Bautista (2016)
This dissertation have as to analyze the transdisplinares practices of the teaching and learning by means of study of case study accomplished in three public schools with students youngs e the adults of the high school of the public web of the state of the São Paulo in that acted during three years as sociology teacher. Parts of the assumption of that the application of the transdisciplinares practices in the class of sociology are right as much to answer at the challenges of conflict management inside classroom demonstrate in the form of the marginalization school, autoritarisme, indiscipline school and triviality violence as for enable livings and experiences focused for full formation of the student, whose commitment is in the human formation and ethical - fundamentals values for the exercises of the citizenship and for job market such as is pointed in the principle of the LDB. For such reasons this project opted to the approach of the complex thought, at the light of the theoretical contributions from the Antony Zabala (2002, 2010) e Edgar Morin (1995, 2011a, 2011b). Alied at this were used the principles of the transdiciplinares practices of the four pillars pointed for the Unesco and offerd by Jaques Delors (2012): to learn at to know, to learn at do , to learn at to do live together, to learn at to live with the others, to learn at to live together et to live at to be. To finish that for means by the narratives of the student of the three schools, the application of the transdiciplinares practices are ables for answed right at the challenge presented to the conflicts in the three schools, at same time that stimulated the dialogue between the discipline of the school schedule et the knows and livings brought for students. Also foment the critical sense, the solidarity, the discipline, the respect, the toleration and the ethical education, provisions necessaries to the human formation, citizenship et to the job market